Kesulitan Guru IPA Kelas VIII Se-Kecamatan Metro Pusat Dalam Merencanakan dan Melaksanakan Asesmen - Okta Via Arisca; Rini Rita T. Marpaung; Berti Yolida (Universitas Lampung, 2017)
This study aimed to identify difficulty of VIII grade science teacher at junior high schools sub district Metro central in academic year of 2016 / 2017 in planning and implementing assessments. The samples were 5 teachers who entirely science teacher class VIII and chosen by sampling saturated technique. Design research was descriptive design. Data difficulty teachers in planning and implementing assessments were obtained from the results of questionnaire and interview of science teachers that were analyzed descriptively. The results of the study showed the average of difficulty experienced teachers in planning and implementing assessments was quite. The main factors that caused teachers had difficulty in planning assessments was make the achievement indicators competence school tuition while that cause teachers had difficulty in implementing assessments was the implementation of the assessments affective domain, especially in observe attitude aspects.Penelitian ini bertujuan untuk mengidentifikasi kesulitan guru IPA kelas VIII SMP Negeri se-Kecamatan Metro Pusat tahun ajaran 2016/2017 dalam merencanakan dan melaksanakan asesmen. Sampel penelitian berjumlah 5 guru yang seluruhnya merupakan guru IPA kelas VIII dan dipilih dengan teknik sampling jenuh. Desain penelitian adalah desain deskriptif. Data kesulitan guru dalam merencanakan dan melaksanakan asesmen diperoleh dari hasil angket dan wawancara pada guru yang dianalisis secara deskriptif. Hasil penelitian menunjukkan rata-rata kesulitan yang dialami guru dalam merencanakan dan melaksanakan asesmen tergolong cukup. Faktor utama yang menyebabkan guru cukup kesulitan dalam merencanakan asesmen adalah menetapkan indikator pencapaian kompetensi peserta didik sedangkan yang menyebabkan guru cukup kesulitan dalam melaksanakan asesmen adalah dalam pelaksanaan asesmen ranah afektif, terutama dalam mengamati aspek sikap.Kata Kunci: asesmen, guru IPA, kesulitan, melaksanakan, merencanakan